PEDAGOGICAL ASPECTS OF IMPROVING THE INFORMATION CULTURE AND MEDIA LITERACY OF YOUNG PEOPLE IN THE CONTEXT OF GLOBALIZATION (ON THE EXAMPLE OF THE REPUBLIC OF KARAKALPAKSTAN) - Allambergenov Aymurza Joldasbaev (The Bioscan, 2025)
In the 21st century, humanity is showing its uniqueness in having success in achieving its scientific and technical achievements. Advanced countries of the world are accelerating scientific and practical discoveries day by day. With a large production potential, countries such as the United States, Japan, the PRC, Russia, England, and Germany are implementing economic, socio-political reforms using the most advanced technologies.